PEMETAAN LAHAN MARJINAL SEBAGAI POTENSI LAHAN PERKEBUNAN CENGKIH DI KECAMATAN KAKAS, KAKAS BARAT DAN LEMBEAN TIMUR DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Devied Raynold Masinambow; Bobby ., Polii; Wiske ., Rotinsulu (Sam Ratulangi University, 2021)
The purpose of the study was to map marginal land to be used as a map of potential clove plantation land in Kakas District, West Kakas District and East Lembean District by using a Geographic Information System (GIS). The research was carried out in 3 sub-districts namely Kakas District, West Kakas District and East Lembean District using satellite imagery, physical observations and by using drones in the field to see areas of marginal land that have the potential to be used as clove plantations. GIS analysis was carried out for 3 months (June – August 2020). The results showed that there is an area of 623,9 hectares that can be used as land for planting cloves in Kakas District, West Kakas District and East Lembean District. With the use of GIS, the community and the government can optimize the marginal land in the 3 sub-districts to be planted so that marginal land can produce.